T-lymphocyte populations in normal and coeliac small intestinal mucosa defined by monoclonal antibodies. Issue 11 (November 1986) - Jenkins, D; Goodall, A; Scott, B B
Abstract : Counts of T-lymphocytes within surface and crypt epithelium and lamina propria of normal and coeliac small intestinal mucosa using an immunoperoxidase method are described and related statistically to changes in mucosal structure determined by quantitative histology. The use of multiple pan-T-lymphocyte and subset antibodies allowed comparison of marker patterns in normal and abnormal mucosa. Total numbers of surface epithelial T-lymphocytes and subtypes were not found to be increased in coeliac disease, but there was an increase in density per unit length of epithelium. Distinctive changes in expression of Leu 1, Leu 2, and Leu 5 by the surface epithelial T-lymphocytes suggest that, although their total numbers are not increased, these cells are not passively crowded but have an active role, possibly as committed cytotoxic lymphocytes. Natural killer cells do not appear to be a major population in normal or coeliac small intestinal mucosa.